Vliv technologie výroby na vlastnosti forsteritu - Nguyen, Martin (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Cílem této diplomové práce je posoudit vliv technologie výroby na vlastnosti forsteritu. Teoretická část obsahuje základní parametry a využití forsteritu v praxi současně s různými možnostmi výroby forsteritu. Hlavní důraz je kladen na charakteristiku surovin pro výrobu a také surovinové možnosti v České republice. Konec teoretické části obsahuje návrh technologie výroby forsteritu, který bude ověřen v praktické části. Praktická část ověřuje použití různých surovin pro složení surovinové směsi. Na vyrobených zkušebních tělesech byla provedena rentgenová difrakční analýza, stanovení pevnosti v tahu za ohybu, součinitele tepelné vodivosti, zdánlivá pórovitost, objemová hmotnost, zdánlivá hustota, nasákavost, trvalé délkové změny v žáru, žárovzdornost, stanovení koeficientu teplotní roztažnosti, únosnost v žáru a odolnost proti náhlým změnám teplot. Na konci praktické části je poté ověření návrhu technologie výroby forsteritu.

The main objective of this thesis is to evaluate the effect of production technology on the properties of forsterite. The theoretical part contains the fundamental parameters and the use of forsterite in the industry together with various possibilities of forsterite production. The main emphasis is placed on the characteristics of the raw materials for production as well as the raw materials possibilities of the Czech Republic. The end of the theoretical part contains a design for the production technology of forsterite, which will be verified in the practical part. The practical part verifies the use of various raw materials for the composition of the raw material mixture. The created test specimens were subjected to the X-ray diffraction analysis, the determination of tensile bending strength, thermal conductivity coefficient, apparent porosity, bulk density, apparent density, water absorption, permanent change in dimension on heating, refractoriness, thermal expansion coefficient, refractoriness under load and the thermal shock resistance. At the end of the practical part is the verification of the design of the production technology of forsterite.
The Effect of Production Technology on the Properties of Forsterite
Keywords: Forsterit; žárovzdornost; technologie výroby; surovinové možnosti; pórovitost; teplotní roztažnost; reakce v pevné fázi; Forsterite; refractoriness; production technology; raw materials options; porosity; thermal expansion; solid state reaction